A physicochemical theory of tip growth - Pelce, Pierre, 1959- (ISTE Press, Ltd. ; Elsevier, 2019)
A Physicochemical Theory of Tip Growth presents the latest information on experimental observations on living organisms, including unicellular algae, hyphae and neurons. These theories are analogous to the ones developed for the growth of nonliving matter, as already exposed by the author in the book.